Artificial Intelligence, English Learning, and Health: Knowledge Optimization, Opportunities, and Challenges for Students - Rizky Amelia; Heppy Mutammimah; Tenny Murtiningsih; Istiqamah Istiqamah; Abdul Halim (Journal of Community Service and Empowerment, 2025)
Artificial Intelligence, English Learning, and Health: Knowledge Optimization, Opportunities, and Challenges for Students. The presence of Artificial Intelligence has brought changes in various fields including healthcare. However, the integration between AI, English language learning and health has not been maximized properly. Thus, this community service activity aims to optimize information about the knowledge, opportunities, and challenges of using AI in the fields of English and health. This community service activity was carried out using the Participatory Action Research method involving 128 students of Universitas Muhammadiyah Banjarmasin. There were 26 students who voluntarily answered the questionnaire before and after the activity. The results of the activity showed that there was an increase in students' understanding of the use of AI in the field of English learning and health. They see the opportunities that AI brings to their current and future healthcare and learning. On the other hand, they realize the challenges faced and know what to do to overcome them. Thus, the education through community service achieved the objectives for which it was designed.